Strong Dominating Set pada Graf Helm Tertutup dan Graf Kincir Angin Belanda - Imanul Umar Hawari; Dafik Dafik; Robiatul Adawiyah (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2023)
A set D⊆ V(G) is a dominating set if every vertex of u ∈ V(G) satisfies one of the conditions u is an element of D or u is a neighbor of some point v ∈ D. The minimum cardinality of dominating set in graph G is called domination number which is symbolized by γ(G). Strong dominating set of a graph G is a subset of V(G) where the condition is that the dominating point must have the greatest degree or be equal to the dominating point. The minimum cardinality of strong dominating set is called strong domination number which is symbolized by γ_st(G). In this study, the graphs to be examined are the closed helmet graph (CH_n) with n≥ 3 and the dutch windmill graph (D_{n,5}) with n≥2.